MENINGKATKAN HASIL BELAJAR KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN BOWLING YANG DIMODIFIKASI PADA SISWA KELAS III SD NEGERI 17 DANGIN PURI TAHUN AJARAN 2017/2018 - I Made Bendi (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
This Classroom Action Research (CAR) aims to explain the application of learning media modifications to bowling games and to describe the learning outcomes of gross motor skills of Grade III students at SD Negeri 17 Dangin Puri in learning the modified bowling game. The study was conducted at 17 Dangin Puri Public Elementary School, North Denpasar District. The subjects of this study were all third grade elementary school students in the second semester of 2017/2018 Academic Year with 38 students, consisting of 23 male students and 15 female students. Data obtained / collected in the form of data directly recorded during PJOK learning takes place. This study uses a cycle model strategy that is planned through two cycles. The actions taken include planning, action, observation, and reflection.The hypothesis in this study was analyzed using quantitative descriptive analysis and qualitative description. Analysis is carried out using computer aids, namely Microsoft Excel program to analyze data by applying formulas, such as frequency distribution, graphs, and average numbers to describe a particular object or variable, so that general conclusions are obtained.The results of class action research found that modified bowling games can improve learning outcomes of rough motoric skills in third grade students of SD Negeri 17 Dangin Puri in Academic Year 2017/2018.